IMPLEMENTASI PRINSIP SOLA SCRIPTURA TEOLOGI REFORMED - Iman Kristina Halawa (Sekolah Tinggi Teologi Arastamar Bengkulu, 2019)
The history of Church reform in the sixteenth century has had an impact on various fields of life, one of which is theology. The Sola Scriptura principle is an important pillar in reform. But at this time there are many elements who claim to apply the principle of Sola Scriptura just because it quotes a verse. There are even individuals in the evangelical church who ignore this principle. Through this paper try to give a thought about the implementation of the principle of sola Scriptura by the Reformers of the XVI century, especially the thoughts of Martin Luther and John Calvin. So that theologians may relearn how to apply the principle of sola scriptura in accordance with the spirit of reform.